(untitled) - Odedokun, Matthew (New York, 2004)
Unu World Institute for Development Economics Research (Unu/Wider) was established by the United Nations University as its first research and training centre and started work in Helsinki, Finland, in 1985. The purpose of the Institute is to undertake applied research and policy analysis on structural changes affecting the developing and transitional economies, to provide a forum for the advocacy of policies leading to robust, equitable and environmentally sustainable growth, and to promote capacity-strengthening and training in the field of economic and social policy-making. Its work is carried out by staff researchers and visiting scholars in Helsinki and through networks of collaborating scholars and institutions around the world.
Keywords: Investments, foreign,Capital movements; Developing countries,Developing countries